Strategic Decision-Making in a Global Context: The Comprehension Effect of Foreign Language Use on Cooperation - Diemo Urbig; Katrin Muehlfeld; Vivien D. Procher; Arjen van Witteloostuijn (Management International Review, 2020)
With increasing globalization comes an increasing number of people communicating in foreign languages when making strategic decisions. We develop a theoretical model in which comprehension constitutes an essential mediator for the effects of using a foreign language on cooperation in global business contexts. To resolve conceptual ambiguities, we separate information processing leading to comprehension from decision-making employing the previously comprehended information. For the first step, we demonstrate how using a foreign language can, depending on individuals' foreign language proficiencies, trigger both lower and higher comprehension. Variation in comprehension is, as a second step and independent of its cause, negatively associated with individuals' tendencies to cooperate. Our experimental results support our theorizing. This study provides new micro-foundations for strategic decision-making and discusses unreliable cooperation as a potentially destructive managerial group dynamic within foreign language contexts.
Keywords: 330; Foreign language use; Information comprehension; Judgment~and decision-making; Strategic decision-making; International management